Satisfaction Index of Employees on Service Quality through Quality Leadership at Three Hospitals B-Type, Central Java Province - Agiwahyuanto, Faik; Suharyo, Suharyo; Ayusasmita, Via; Widjasena, Baju (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2021)
One achievement of leadership style is job satisfaction. Therefore, this research aims to analyze the effect of job satisfaction on service quality through the leadership of hospital directors at various Type B Regional General Hospitals. This was done by processing data contained in the Decree of the Minister of Administrative Reform (Kepmenpan) No. Kep/25/M.PAN/2/2004. The research had a cross sectional study design and 500 samples who were employees from both civil servants and BLUD (300 respondents from hospital B type at Semarang city, 100 from Jepara regency, and 100 from Kendal regency). A simple random sampling was the technique used to obtain the subjects. Data processing and analysis was performed using the Community Satisfaction Index of Government Agencies Service Units. The results show that employee satisfaction index, service quality and the quality leadership of hospital B type at Semarang city and at Kendal Regency is decreasing. But hospital B type at Jepara regency is increasing. Therefore, a transformational leadership style can increase employee satisfaction.